The influence of diatopic variation and first language on the perception of emotions in the Basque language - Gaminde, Iñaki; Etxebarria, Aintzane; Aurrekoetxea, Gotzon; Garay, Urtza; Romero, Asier (Círculo de Lingüística Aplicada a la Comunicación, 2015)
The aim of this study is to determine the influence of diatopic variation and first language on emotions perception in Basque language. For this purpose simulated emotions have to be recorded from some young women from Basque Country. The corpus features 24 oral recordings, is the same phrase and semantically neutral, with this corpus was designed a specific test for research. 349 young participants from seven Basque territories were divided into two groups according to first language, some of them belong to group A (Basque) and the others to group B (Spanish or French), and these participants had to identify the intended basic emotion from an audio. According to the test results, sadness is better perceived emotion, and anger the worst, because of they are phonetically more similar. With regard to participants’ first language, differences are statistically significant, inasmuch as A group participants correctly matched more items than group B. According to their source, Northern Basque Country correctly matched more items than the participants from Navarra; anyway the current results suggest that the differences are not statistically significant.
Keywords: Prosody; diatopic variation; perception; emotions.